Hubungan Kompetensi Kepribadian Guru Dengan Motivasi Belajar Siswa Kelas VIII Pada Mata Pelajaran Fiqh Di MTs PONPES Nurul Islam Kampung Baru Toar - Desy Andriani; Sarmidin Sarmidin; Wigati Iswandhiari (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Teacher personality in teach directly or indicertly will have on motivation student learning both positive and negative. If teachers personality competencies has been mastered by the teachers so a teacher can motivation students in the learning process. But in reality teachers who have good personality competence have not been ablebto build student motivation in MTs PONPES Nurul Islam Kampung Baru Toar, from the results pre reseach wherebthe teacher already has good personality competencies but students learning motivation is still low. Then research has done research in MTs PONPES Nurul Islam Kampung Baru Toar to see how the teacher personal competence correlates with student motivation. Research conducted is quantitative research with make korelasi and product moment . Research us observation, teachniques, interview, questionnaires and documentation.From this study incan be concluded that the relationship between teacher’s personality competence and student motivation of 0,6 with “ enough categories which influences the teacher’s personal competence and students motivation is sometimes the teacher is not able to create a fun an happy classroom atmosphere, mos students have not been able to solve difficult questions, not ready to accept learning to be taught and enthusiasm in the learning process. Keyword :influences the teacher’s personal competence and studentsmotivation